Summary of evidence on prevention and management of bladder dysfunction in patients after radical hysterectomy - Chao Zeng; Yuanyuan Mi; Fulan Wang; Qinghua Zhao; Mingzhao Xiao; Feng Xiao; Yan Hu; Lin Wang; Fang He (Wiley, 2024)
Abstract Aim To retrieve, analyse and summarize the relevant evidence on the prevention and management of bladder dysfunction in patients with cervical ancer after radical hysterectomy. Design Overview of systematic reviews. Methods 11 databases were searched for relevant studies from top to bottom according to the '6S' model of evidence‐based resources. Two independent reviewers selected the articles, extracted the data and appraised the quality of the included reviews based on different types of evaluation tools. Results A total of 13 studies were identified, including four clinical consultants, four guidelines, four systematic reviews and one randomized controlled trial. 29 best evidence were summarized from five aspects, including definition, risk factors, assessment, prevention and management.